Both GA2, GM2, and GD2 synthases and GM1b, GD1a, and GT1b synthases are single enzymes in Golgi vesicles from rat liver. - Pohlentz, G (1988)
Competition experiments using lactosylceramide, ganglioside GM3 and ganglioside GD3 as substrates, as well as mutual inhibitors for ganglioside N-acetylgalactosaminyltransferase, in Golgi vesicles derived from rat liver suggested that N-acetylgalactosamine transfer to these three respective compounds, leading to gangliosides GA2, GM2, and GD2, respectively, is catalyzed by one enzyme. Analogous studies with gangliosides GA1, GM1, and GD1b as glycolipid acceptors in sialyltransferase assays indicated GM1b, GD1a, and GT1b synthases to be identical. These results are incorporated into a model for ganglioside biosynthesis and its regulation.